Is Cross-Shareholding Conducive to Corporate Sustainability? Evidence From the Environmental Investment of Chinese Listed Firms - Tian, Jinfang; Cao, Wei; Ji, Xuzhao (Frontiers in Psychology, 2021)
This paper examines the impact of cross-shareholding on corporate environmental investment using Chinese listed firms from 2014-2019 as the research setting. The results show that there is a positive impact of cross-shareholding on corporate environmental investment. The finding remains robust to a battery of robustness checks. In addition, the heterogeneity analysis illustrates that the positive impact of cross-shareholding on corporate environmental investment is more pronounced in state-owned firms and high-polluting industries when compared to non-state-owned firms and low-polluting industries, respectively. This study extends the research on cross-shareholding and provides practical implications for corporate sustainable development.